KNOWLEDGE, SKILLS AND ATTITUDES OF TEACHERS ON INCLUSIVE EDUCATION AND ACADEMIC PERFORMANCE OF CHILDREN WITH SPECIAL NEEDS - Baguisa, Leonila R; Ang-Manaig, Karen (PEOPLE: International Journal of Social Sciences, 2021)
The study aimed to determine the knowledge, skills and attitudes of teachers on inclusive education and academic performance of children with special needs in public elementary schools in the District of Bay. It utilized the descriptive-correlational and descriptive survey method to test significant relationship among teachers’ knowledge, attitude, and skills in inclusive education and pupils formative and periodical test performance. The respondents of the study are the selected inclusive education teachers or the SPED teachers of the Bay District and Division of Laguna. The statistical treatment applied are r- value, p-value, mean percentage and frequency. It sought to identify and answer the mean level of the demographic profile of the respondents and knowledge, skills and attitude on inclusive education and academic performance of pupils with special needs in terms of formative and periodical test.The study has proven that there is significant relationship between and among the knowledge and attitude of the respondents and inclusive education. Therefore, the hypothesis is rejected. Based on the findings and conclusions of the study it is highly recommended that: The schools practicing inclusive education must prioritize teacher applicants with experience in dealing with students with special needs. The school administration must provide more trainings in inclusive education to general educators who are teaching students with special needs. There must be more evident collaboration among the local community education committee, parents, teachers and the school in addressing the concerns of inclusive education in the school level.